Movimientos datificados y colaboración estudiantil en Instagram a partir del contexto brasileño (Miscelánea) - Paula, Ana Lidia Resende (2025)
This article takes part in an ongoing work whose purpose is to analyze the communication collaborative practices mediated by algorithms, through the observation of the construction of the communicative content on the Instagram account of the União Nacional dos Estudantes (UNE), social movement that represents the Brazilian university students. As part of an ethnographic approach, in this exploratory stage, we used a combination of netnographic and cartographic methods to collect and systematize the analyzed data. We collected 78 pieces of content published on the @uneoficial profile on Instagram between August 1 and 31, 2024 - a period that includes Student’s Day, celebrated on August 11, a date that also coincides with UNE’s anniversary. The preliminary results identify the main participating actors and present an initial systematization of the materialization of student collaboration on Instagram: the demarcation of collaborators’ profiles in the caption texts and the use of the Instagram Collabs tool, an Instagram tool whose main objective is to foster collaboration between accounts. Thus, we discuss how students tactically appropriate the platform’s tools to build their practices of resistance, socialities, and citizenship. Furthermore, we initiate a debate on how collaboration materialized by algorithmic mediations can help us advance analytical perspectives on datafied social movements.